Islamic mathematics - Azram, Mohammad; Daoud, Jamal Ibrahim (2013)
The present doldrums position and state of decadence, internal differences, external aggression (geographical and ideological), lack of self-confidence and dependence, illiteracy, political instability, economic disaster, lack of knowledge and wisdom, back benchers in science and technology, education, medicine, trade and business, banking system and defensive incapability of Muslim World prompted me to look at our principal sources of inspiration, which are, the Qur’an, Sunnah of the Prophet (SAW), and examples of the “enlightened Caliphs” and see what is Islam’s view about seeking knowledge, technology and inventions in general and mathematics’ education in particular. We will discuss the nature of mathematics and its scientific status. We will highlight the position of mathematics in Islamic classification of knowledge. We will also discuss the current state of mathematics and future suggestions. We have gathered together some of these impressions; these are all tentative, nothing final about them, but these are here nonetheless.